Payment models and the sustainability of community pharmacy practice: a qualitative interview study with community pharmacists - Kelly Ann Schmidtke; Terri Warholak (Journal of Pharmaceutical Policy and Practice)
Background The sustainability of community pharmacies in the United States depends, in large part, on policies enacted by the Centers for Medicare and Medicaid Services (CMS). In 2003, CMS policy allowed retrospective direct and indirect remuneration (DIR) fees to manage costs. From 2024, only prospective DIR fees are permitted. The current study explores how existing payment models have impacted practice and how the policy change might impact future practice.Methods and Materials Semi-structured qualitative interviews were conducted with community pharmacists knowledgeable about third-party payment and reimbursement practices in the state of Missouri. Interviews were recorded, transcribed, and reflectively analysed to identify broad themes. Final codes were applied to direct quotes. Participants checked transcripts and drafts of the manuscript for accuracy and completeness.Results Twelve pharmacists (11 males) with self-expressed knowledge of fees impacting their practice(s) participated. The pharmacists owned or worked for community pharmacies. The median percentage of patients served on Medicare Part D was 35% (range 24% to 60%). Four main themes and one overarching theme were identified. Theme 1 describes a sense of being punished for the basic component of pharmacy practice, i.e. safely dispensing prescription medications. Theme 2 describes a diversification of the business model to subsidise losses on the basic component. Theme 3 describes anticipated challenges given the policy change. Theme 4 describes what may be needed to achieve payment reform. The overarching theme describes the purpose of community pharmacy, including who community pharmacists are and who they serve, i.e. their community.Conclusion Community pharmacies require a financially viable and sustainable business model to deliver the legally required basic component of practice: safely dispensing prescription medications. Legislative action could help to ensure community pharmacies are appropriately compensated for work at the federal and state levels. Where services beyond the basics cost-effectively benefit public health, payment models could support them.